Modelling the Impact of Decomposed Disease-Induced Dead Cashew Plants on Fusarium Wilt Dynamics in South-Eastern Tanzania - Fatu Chilinga; Alfred K. Hugo (Journal of Mathematical and Fundamental Sciences, 2023)
Cashew Fusarium wilt disease transmitted by Fusarium oxysporum is dangerous and destroys many cashew plants in Tanzania. The effect of this disease leads households and the government to experience a decrease in overall cashew production and income due to this disease’s capacity to harm cashew plants. This study aimed to ascertain the role of Fusarium wilt-decayed disease-induced dead plants in spreading the disease among cashew plants. A mathematical model was created based on the dynamics of the disease and a stability analysis was conducted using theories of ordinary differential equations. Data from two regions in Tanzania, Lindi, and Mtwara, were used in model fitting and parameter estimation. Additionally, the parameters were estimated using maximum likelihood estimation (MLE). The outcome suggests that the disease’s prevalence and spread increase during an outbreak as decomposed diseased-induced dead plants contribute to the saturation of chlamydospores in the soil.